2011
DOI: 10.1089/vbz.2010.0253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection ofAnaplasma phagocytophilumin Ixodid Ticks in Hebei Province, China

Abstract: A total of 3696 Ixodid ticks, collected from Hebei Province, China, were examined by a nested polymerase chain reaction for the presence of Anaplasma phagocytophilum. Forty-three (15.4%) of 280 pools tested, including 39 (14.6%) of 267 Haemaphysalis longicornis and four (30.8%) of 13 Dermacentor nuttalli, were positive, but no significant difference was found between D. nuttalli and H. longicornis (p>0.05). Sequence and phylogenetic analyses of 16S rRNA gene indicated that A. phagocytophilum in China is geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Our results are consistent with other PCR studies from China [1, 610, 12, 13] showing that domestic ruminants from the country are infected with a range of Anaplasma and Ehrlichia spp. Differences in the prevalence of animals on the farms we studied were most likely due to differing husbandry practices and tick exposure, with dairy animals and water buffaloes raised intensively having the lowest levels of positivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with other PCR studies from China [1, 610, 12, 13] showing that domestic ruminants from the country are infected with a range of Anaplasma and Ehrlichia spp. Differences in the prevalence of animals on the farms we studied were most likely due to differing husbandry practices and tick exposure, with dairy animals and water buffaloes raised intensively having the lowest levels of positivity.…”
Section: Discussionsupporting
confidence: 93%
“…we detected with our 16S rRNA FRET-qPCR, we could confirm the accuracy of the qPCR in detecting A. marginale and A. ovis . Anaplasma marginale was one of the most common Anaplasma species we detected with the 16S rRNA FRET-qPCR along with A. phagocytophilum which has also already been described in China where it appears to be common in ruminants [7, 11, 12, 34]. Anaplasma phagocytophilum is the agent of tick-borne fever of ruminants and is transmitted by Dermacentor silvarum , Haemaphysalis concinna, H. longicornis , and Ixodes persulcatus in China [35, 36].…”
Section: Discussionmentioning
confidence: 66%
“…Although, A. phagocytophilum was detected in the genera of Ixodes , Dermacentor , and Haemaphysalis , I. persulcatus may play the most important role in the transmission of the bacterium in northeastern China, due to the high infection rate in the tick species and its high abundance. In Hebei province, A. phagocytophilum was detected in H. longicornis and D. nuttalli , where H. longicornis is the predominant tick species for the transmission of this pathogen (Yaxue et al, 2011). Phylogenetically, A. phagocytophilum detected in the study was more likely to infect ruminants (Yang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that this tick species transmitted a variety of pathogens [33,34], including Babesia microti [35], Ehrlichia chaffeensis [36], Anaplasma bovis [37], A. phagocytophilum [38], C. burnetii [39], Spotted fever group rickettsiae [40], and Borrelia burgdorferi [41]. With regard to the human health and economic significance, pathogens carried by H. longicornis have been well investigated in China [42-47].…”
Section: Introductionmentioning
confidence: 99%